Estimation of Bioavailability of Copper, Lead and Zinc in Municipal Solid Waste and Compost - Szymanski, Kazimierz; Janowska, Beata; Sidelko, Robert (Asian Journal of Chemistry, 2016)
The influence of composting on the concentrations of copper, lead and zinc from municipal solid waste is conducted. The composition of composts obtained from municipal wastes by biothermic method DANO in Kolobrzeg was investigated. IN the waste, copper occurs in the not easily available fractions. Most of the metal is bound in the organic and residual forms. While lead occurs in the available fractions and was partitioned between organic and carbonate-bound fractions. During the composting process, the major portions of lead were found in the oxide and residual fractions. Zinc was mainly associated with Fe/Mn oxides and carbonate-bound fraction. During the composting process amount of metals decreases in the exchangeable and organically bound fractions. In general, all metals concentrations increased in the final compost due to decomposition of organic matter. Metal distributions in the different chemical forms were dependent on composting age, total metal concentrations in the compost, pH, contents of organic matter and concentrations of compounds of Ca and Fe. In mature compost, amount of metals increases in the low mobile and residual fractions.